Theoretical Framework for the Green Recovery Model for Forest and Farm Producer Organizations in Vietnam PostNatural Disasters: Towards Sustainable Development and Resilience Enhancement - Hong Hai Pham; Kim Lien Le (European Scientific Journal, ESJ, 2025)
Green recovery is not only an immediate response to natural disasters but also a crucial strategy for strengthening the resilience of rural ecosystems and communities in the face of increasing climate change. This study proposes a theoretical framework for a green recovery model, particularly suited to forestry and agricultural organizations affected by natural disasters, with a specific focus on the case of Typhoon Yagi in Vietnam.The analysis is based on a systematic review of the methodological literature outlined by Jesson et al. (2011), incorporating more than 40 peer-reviewed academic publications from databases such as Scopus, Web of Science, Elsevier, and Emerald. The selection process follows strict criteria to ensure data relevance and accuracy. The studies analyzed, including those by OECD (2020), UNEP (2020), Barbier (2020), and Phillips & Heilmann (2021), provide valuable insights into green recovery policies, sustainable resource management strategies, and international best practices.The results indicate that an effective green recovery model for forestry and agricultural organizations must be built upon five fundamental pillars: (1) sustainable management of natural resources, (2) sustainability-oriented economic and financial policies, (3) technological innovation and the transition to renewable energy, (4) active community involvement and the strengthening of Forest and Farm Producer Organizations (FFPOs), and (5) circular economy development to minimize environmental impacts. Implementing such a model would not only accelerate disaster recovery but also facilitate the transition to a more resilient, low-carbon economy.From a practical perspective, the study offers recommendations for public institutions and international organizations to integrate green recovery into long-term development strategies. In particular, it emphasizes the need to invest in green infrastructure, promote the adoption of sustainable technologies, and implement eco-certification programs to enhance the global competitiveness of FFPOs.In conclusion, green recovery is not only a means of mitigating the impact of natural disasters but also a strategic tool for fostering sustainable and inclusive development. Further research is needed to assess the effectiveness of different green recovery strategies within specific socio-economic contexts and to refine policies that support FFPOs.